2015
DOI: 10.5430/jha.v4n6p56
|View full text |Cite
|
Sign up to set email alerts
|

Urban-rural difference in patients utilizing the service of telehealthcare

Abstract: There are concerns about the unbalanced distribution of healthcare resources between rural and urban areas. There have been attempts to use existing healthcare resources more effectively through telehealthcare. Usability is an important indicator for evaluating patient behavior and determining service improvements. Nevertheless, usability has not been studied extensively enough. This study analyzed the usability differences between urban and rural areas in Taiwan for a web portal used in a telehealthcare progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In a skin tumor screening context by Hameed et al., 23 the diagnostic accuracy of clinical dermoscopic image tele‐evaluation was evaluated. Using images collected over time via a mobile phone camera, they demonstrated that clinical image tele‐evaluation could be a viable method for mobile tumor screening.,Chen 24 outlined diverse systems for classifying and categorizing skin lesions, focusing on pattern classification of dermoscopic images within a perceptually uniform model. Various techniques for lesion segmentation were defined by Rashid, 25 including clustering, edge‐based, region‐based, and active contour methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a skin tumor screening context by Hameed et al., 23 the diagnostic accuracy of clinical dermoscopic image tele‐evaluation was evaluated. Using images collected over time via a mobile phone camera, they demonstrated that clinical image tele‐evaluation could be a viable method for mobile tumor screening.,Chen 24 outlined diverse systems for classifying and categorizing skin lesions, focusing on pattern classification of dermoscopic images within a perceptually uniform model. Various techniques for lesion segmentation were defined by Rashid, 25 including clustering, edge‐based, region‐based, and active contour methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chen et al [5], with respect to unbalanced healthcare services between rural and urban areas, analyzed the importance of usability indicators for a web portal in a tele-healthcare program. The authors collected data from urban and rural areas in Taiwan, and showed that urban patients tended to use the web portal more often than rural patients, providing more advanced information.…”
Section: Related Workmentioning
confidence: 99%
“…It offers mechanisms for centralizing specialists, reducing costs for specialty care, and supporting primary care clinician needs in the urban and suburban areas these typically serve [5-9]. The possible benefits of using these systems have resulted in an increased interest in telemedicine.…”
Section: Introductionmentioning
confidence: 99%
“…Although playing an important role in addressing the health issues of patients living in underserved and rural areas, telemedicine is now attracting attention beyond these limited regions. It offers mechanisms for centralizing specialists, reducing costs for specialty care, and supporting primary care clinician needs in the urban and suburban areas these typically serve [ 5 - 9 ]. The possible benefits of using these systems have resulted in an increased interest in telemedicine.…”
Section: Introductionmentioning
confidence: 99%